(untitled) (Bangladesh Journal of Agricultural Research, 2010)
The study was conducted to validate the Drought Assessment (DRAS) model developed by the Center for Environmental and Geographic Information Services (CEGIS) for irrigation scheduling of wheat (variety: Shatabdi). The performance of the model was compared with the results obtained from the BARI recommended irrigation schedule. The field experiments were carried out during the years 2005-2006 through 2007-2008 in two agro-ecological zones. The locations were RARS, Jamalpur under agro-ecological zone 9 and farmers’ field of FSR site, OFRD, Barind, Rajshahi under agro-ecological zone 26. Six different irrigation treatments including one rainfed with three replications were considered for the study. In respect of yield, BARI recommended irrigation practice performed better in Jamalpur (3.642 t/ha on average). Application of net irrigation requirement (NIR) as per DRAS model based on reported value yielded highest (3.598 t/ha on average) in the Barind area, Rajshahi. However, the yields from all irrigated treatments were very close to each other. From three years’ study, the model performance was found quite satisfactory for irrigated wheat, especially in drought prone areas like Barind, Rajshahi. In respect of water productivity, the model performed almost similar to the BARI recommended practice in Jamalpur. It performed better in Barind region where irrigation water was used by the crop more efficiently. Keywords: DRAS model; irrigation; wheat. DOI: 10.3329/bjar.v35i3.6447 Bangladesh J. Agril. Res. 35(3) : 403-411